Rolling vesicles: From confined rotational flows to surface-enabled motion - Paula Magrinya; Pablo Palacios-Alonso; Pablo Llombart; Rafael Delgado-Buscalioni; Alfredo Alexander-Katz; Laura R. Arriaga; Juan L. Aragones (Proceedings of the National Academy of Sciences, 2025)
Friction forces are essential for cell movement, yet they also trigger numerous active cellular responses, complicating their measurement in vivo. Here, we introduce a synthetic model designed to measure friction forces between biomimetic membranes and substrates. The model consists of a vesicle with precisely controlled properties, fabricated via microfluidics, encapsulating a single ferromagnetic particle that is magnetically driven to rotate. The rotation of the particle generates a confined rotational flow, setting the vesicle membrane into motion. By adjusting the magnetic field frequency and vesicle size, the rotation frequency of the vesicle can be finely controlled, resulting in a rolling vesicle that functions as an effective tribological tool across a wide frequency range. At low frequencies, molecular contact between the membrane and substrate dominates frictional interactions, which enables determination of the contact friction coefficient. At higher frequencies, lubrication becomes predominant, causing the vesicles to slip rather than roll. Adjusting membrane fluidity and incorporating specific ligand–receptor interactions within this model will enable detailed studies of frictional forces in more complex biomimetic systems, providing key insights into the mechanisms of cell movement and mechanotransduction.